A transição profissional dos licenciados em Sociologia pela FLUP : novos resultados em 2006 - Parente, Cristina (2012)
This article seeks to reflect on the importance of a university degree in the labor market. Regarding the profound changes occurring on the economic sphere, the transition of young graduates in the labor market gets a configuration increasingly insecure and unstable. According to that, this article identifies and discusses various aspects which determine the employability of graduates in sociology from the Faculty of Arts of University of Porto, through the data collected in 2006 by Employment Observatory of Graduates in Sociology, and in continuity with the two previous studies which resulted in two articles, conducted in 1998 and 2003, and published in 2001 and 2004 respectively.